Telecommunications and industrial development - Isaksson, Anders (UNIDO ViennaAT, 2010)
Addresses whether telecommunications infrastructure exerts any explanatory power as to why some countries have managed to industrialise while others have failed to do so. Concludes that for most countries, it pays to invest in telecommunications infrastructure.